PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP MATERI PERBANDINGAN - Sugianto Sugianto (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
The low mathematical problem-solving ability of junior high school students due to the dominance of conventional learning that does not connect concepts with reality is the background of this study. The study aims to analyze the effect of the Realistic Mathematics Education (RME) approach on problem-solving ability in comparative material. The method used is a quantitative quasi-experimental type with a nonequivalent control group design. Data analysis was carried out through t-tests and N-Gain calculations. The research findings show that the average posttest of the experimental class reached 78.79, significantly superior to the control class of 71.16 with a significance value of 0.015. The increase in problem-solving ability in the experimental class is in the moderate category with an N-Gain score of 0.47, where the indicator for drawing conclusions experienced the highest increase of 0.54 and the indicator for solving problems the lowest of 0.41. The main conclusion of this study confirms that the application of the RME approach has a positive effect and is more effective in improving students' mathematical problem-solving abilities compared to conventional learning, so it can be used as an alternative relevant learning strategy. ABSTRAK Rendahnya kemampuan pemecahan masalah matematis siswa SMP akibat dominasi pembelajaran konvensional yang kurang menghubungkan konsep dengan realitas menjadi latar belakang penelitian ini. Penelitian bertujuan untuk menganalisis pengaruh pendekatan Realistic Mathematics Education (RME) terhadap kemampuan pemecahan masalah pada materi perbandingan. Metode yang digunakan adalah kuantitatif jenis kuasi eksperimen dengan desain nonequivalent control group. Analisis data dilakukan melalui uji-t dan perhitungan N-Gain. Temuan penelitian menunjukkan bahwa rata-rata posttest kelas eksperimen mencapai 78,79, lebih unggul secara signifikan dibandingkan kelas kontrol sebesar 71,16 dengan nilai signifikansi 0,015. Peningkatan kemampuan pemecahan masalah pada kelas eksperimen berada pada kategori sedang dengan skor N-Gain 0,47, di mana indikator menarik kesimpulan mengalami kenaikan tertinggi sebesar 0,54 dan indikator menyelesaikan masalah terendah sebesar 0,41. Simpulan utama penelitian ini menegaskan bahwa penerapan pendekatan RME berpengaruh positif dan lebih efektif dalam meningkatkan kemampuan pemecahan masalah matematis siswa dibandingkan pembelajaran konvensional, sehingga dapat dijadikan alternatif strategi pembelajaran yang relevan.